2018
DOI: 10.1155/2018/4357647
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA LOC441178 Reduces the Invasion and Migration of Squamous Carcinoma Cells by Targeting ROCK1

Abstract: In recent years, long noncoding RNAs (lncRNAs) have been reported to have significant regulating effect in human cancer development. Previous studies suggested that dysregulation of lncRNA 441178 (LOC441178) is possibly associated with oral squamous cell carcinoma (OSCC). The postoperative survival time was significantly prolonged in the high-grade OSCC patients with high LOC441178 expression compared with those with low LOC441178 expression, which indicated that LOC441178 may act as a prognostic marker and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…LncRNAs can modulate gene expression to influence the biological activities of carcinomas. 19,20 As FUT4 is an important oncogenic factor in the progression of human carcinomas, we first measured FUT4 expression in MM cells and discovered that FUT4 expression was lifted in MM cells and tissues compared to that in nPCs cells and nontumor tissues (Figure 2A and Figure S1F). In U266 and H929 cells, FUT4 expression was accordingly lowered with shHOXB-AS1#1 treatment ( Figure 2B).…”
Section: Hoxb-as1 Regulatedmentioning
confidence: 99%
“…LncRNAs can modulate gene expression to influence the biological activities of carcinomas. 19,20 As FUT4 is an important oncogenic factor in the progression of human carcinomas, we first measured FUT4 expression in MM cells and discovered that FUT4 expression was lifted in MM cells and tissues compared to that in nPCs cells and nontumor tissues (Figure 2A and Figure S1F). In U266 and H929 cells, FUT4 expression was accordingly lowered with shHOXB-AS1#1 treatment ( Figure 2B).…”
Section: Hoxb-as1 Regulatedmentioning
confidence: 99%
“…The dysregulation of LINC02487, alternatively known as LOC441178, was detected by transcriptome analysis and verified by RT-PCR in OSCC [57]. Xu [58] et al found that LINC02487 could sponge coiled-coil-containing protein kinase 1 (ROCK1) in OSCC, and that OSCC patients with a high expression of LINC02487 would have a longer survival time, which was in accordance with our result and also suggested that LINC02487 could be a new therapeutic target and prognostic indicator for TSCC. To the best of our knowledge, no relevant studies found that LINC02028, LOC101927503, LOC349160 and LINC02560 existed in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In MHD patients, a low physical activity level is closely related to poor prognosis [ 4 ]. Several studies have confirmed the relationship between a low physical activity level and the increased risk of cardiovascular disease in MHD patients [ 5 , 6 ], which was the leading cause of morbidity and mortality in these patients [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%